Avaliação de desgaste mecânico em agulhas de lingueta aplicadas em tear circular - Andrade, Jônata Silva do Nascimento (2022)
Knitted textile structures are widely used by mankind, and they are produced on machines with a mechanical sliding system. The needles fit into trick wall (thin grooves) and slide over them in an alternating motion so that loops can be formed. This system naturally causes friction and wear on the needles and trick wall, which makes it necessary to replace these parts over time. This research consists of an evaluation of wear on latch needles, in order to contribute to a better understanding of the wear mechanism that occurs in this system. In order to analyze the abrasion on the needle butt, a mechanical adaptation was made in a machine that simulates abrasion on fabrics, so that a tribological pair was formed between the needle butt and a cam, of the same model used in circular knitting machines. To analyze the abrasion on the needle stem, a small diameter circular knitting machine was used, with needles placed in random trick walls, analyzing the abrasion from the contact between the tribological pair needle stem and trick wall. For both cases, needles were separated and subjected to the following tests: 15,000, 30,000, 45,000, and 60,000 dry cycles, with Silvertex 32B oil lubrication (for circular knitting machines) and with Silvertex 32B oil lubrication + metal conditioner, at a single speed of 260 cycles per minute. The temperature was monitored with a thermocouple fixed near to the friction zone. The samples were analyzed by portable digital microscope image, Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDS). As a result, it was possible to verify the points of the needle most susceptible to abrasion. It was found that internal clearances in the trick wall influence the wear regions of the needle stem and that deformities in the trick wall influence the wear intensity of the needle butt. The temperature increment is higher in cycles without lubrication. So the lubricant attenuate the temperature increase and the metal conditioner act as abrasion reducer.